Recovery of rare earth elements from coal fly ash by integrated physical separation and acid leaching. (June 2020) - Pan, Jinhe; Nie, Tiancheng; Vaziri Hassas, Behzad; Rezaee, Mohammad; Wen, Zhiping; Zhou, Changchun
Abstract: Coal fly ash (CFA) is one of the most promising secondary sources of rare earth elements and yttrium (REY). This research first studied the modes of occurrence of REY in CFA collected from a China's power generation plant which utilizes a coal feedstock with an elevated REY content. The fact that rare earth minerals remain in CFA and REY associate with metal oxides was proved by emission-scanning electron microscope with an energy-dispersive X-ray spectrometer. The technical feasibility of recovery of REY from CFA was then studied through conducting various physical separation methods followed by acid leaching. It was found that REY are concentrated in fine particle size, non-magnetic and middle density fractions. Using combined physical separation processes, the REY of CFA was enriched from 782 μg·g −1 to 1025 μg g −1 . The acid leaching process was optimized for various parameters via the Taguchi three-level experimental design. Upon optimization, the physical separation product was leached at the optimum condition and 79.85% leaching efficiency was obtained. Based on the obtained results, a conceptual process flowsheet was developed for recovery of REY from CFA. Such recovery maximizes REY resources utilization and enhances sustainability of CFA disposal. Graphical abstract: Based on REY occurrence theory and results of physical separation and acid leaching, an integrated procedure is shown in graphical abstract, which contains couple parts (classification, magnetic separation, leaching and solid/liquid separation) done and two ongoing parts: roasting for sample with hard leaching and purification from leachate. Image 1 Highlights: REY mode of occurrence in coal fly ash was studied and confirmed. REY content of 1025 μg/g in final product was achieved via physical processing. Integrated physical separation and acid leaching process was suggested for REY recovery.